2013
DOI: 10.1007/s10195-012-0223-x
|View full text |Cite
|
Sign up to set email alerts
|

Silicone ring tourniquet versus pneumatic cuff tourniquet in carpal tunnel release: a randomized comparative study

Abstract: BackgroundThe aim of the present study was to compare the pain levels resulting from the use of a silicone ring tourniquet (SRT) to those resulting from the use of a classic pneumatic cuff tourniquet (PT) in patients undergoing carpal tunnel release under local anesthesia.Materials and methodsFifty patients that underwent carpal tunnel release under local anesthesia were randomized using the technique of stratified randomization by minimization. A forearm tourniquet was applied: a standard PT was used in 25 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Drosos et al 9 reported the use of SRT in 362 elective operations and 174 trauma cases Pereira et al 16 reported no clinically significant advantage in a retrospective comparison of carpal tunnel syndrome cases operated using a SRT versus a PT. However, Drosos et al 11 in a prospective randomised study of carpal tunnel syndrome cases, observed a significant decrease in pain evaluation, suggesting less soft tissue damage. To our knowledge, previous to our study, only two evaluations of the SRT during TKA have been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Drosos et al 9 reported the use of SRT in 362 elective operations and 174 trauma cases Pereira et al 16 reported no clinically significant advantage in a retrospective comparison of carpal tunnel syndrome cases operated using a SRT versus a PT. However, Drosos et al 11 in a prospective randomised study of carpal tunnel syndrome cases, observed a significant decrease in pain evaluation, suggesting less soft tissue damage. To our knowledge, previous to our study, only two evaluations of the SRT during TKA have been reported.…”
Section: Discussionmentioning
confidence: 96%
“…However the Hemaclear 1 tourniquet caused less pain than the pneumatic tourniquet when placed on the arm [11]. The second showed that the conventional pneumatic tourniquet caused more pain after 5 minutes of application [12]. The third found greater pain with the Hemaclear 1 tourniquet [13].…”
Section: Discussionmentioning
confidence: 96%
“…Studies comparing the raw material of the cuff with an aim to reduce the complications associated with tourniquet use have rarely been reported. Several studies have reported a silicone ring tourniquet as an alternative to the standard pneumatic tourniquet [ 23 25 ]. A recent randomized comparative study compared silicone ring tourniquets to conventional cuff tourniquets in TKA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%